Mengungkap Hubungan Penguasaan Konsep dengan Kemampuan Mahasiswa Menggunakan Horizontal Translation across Mode pada Materi Fotosintesis - Any Fatmawati; Husnul Jannah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Concept mastery is a person's basic ability to bring up other abilities in learning. Therefore it is necessary to conduct research on the relationship between mastery of concepts and other content such as the ability to use representations horizontally, which is referred to as cross-mode horizontal translation or HTM. One indicator of someone who has representational abilities is being able to express biological concepts by using representations horizontally. The purpose of this study was to determine the correlation of student mastery of concepts to representational abilities, especially HTM. The research method is a correlational analysis between concept mastery and HTM abilities. The research subjects were 37 students who had taken the Plant Physiology course at the Biology Education Study Program at the Mandalika University of Mataram, in the even semester of the 2019/2020 academic year. Data was collected using essay tests that had been assessed by experts and declared fit for use. Data analysis used a regression test at a significance level of 5%. The results showed that there was a correlation between concept mastery and students' representation abilities in interpreting scientific phenomena horizontally (HTM) in photosynthetic materials. The amount of loan provided by understanding the concept of representation ability is 55.70%.